Is Corruption ‘Grease’ Or ‘Sand’ in the Wheels of Foreign Direct Investment Inflows in the South Asian Economies? - Bhavan, Thangamani (Asian Development Policy Review, 2020)
The objective of this study is to investigate whether the corruption serves as ‘grease’ or ‘sand’ in the wheels of Foreign Direct Investment inflow in South Asian Countries, namely Sri Lanka, India, Pakistan, Nepal, and Bangladesh during the period from 2002 to 2018. Using annual time series panel data, the Random Effect method is employed for the analysis. The results derived from the analysis suggest that FDI inflows improve when the perception of the investors over the level of corruption in these countries is favorable to the investment. Therefore, improvement in the perception of corruption towards clean facilitates the foreign direct investment inflow in these countries.